Study on Cement Brick Properties with Composition of Sago Fine Waste (SFW) as Filler - Adnan, Suraya Hani; Abdul Wahab, Norhayati; Mohd Razi, Siti Balqis; Osman, Mohamad Hairi; Wahee Anuar, Mohamad Nor Akasyah (International Journal of Integrated Engineering, 2024)
This paper presented the potential of Sago Fine Waste (SFW) in the production of brick. Sago is well recognized as a basic material in making local food. In Malaysia, Sarawak has the largest sago palm plantation areas and currently is known as one of the world’s largest exporters of sago starch. However, due to the strong demand for sago starch in the global market, tons consumption of sago was subsequently increasing the amount of waste generated. Usually, the waste of the sago processing is left on the riverbank or river stream. Therefore, the utilization of sago waste in brick was approached to contribute to the quality of the environment and improve the improper treatment of the waste. In this study, SFW was used as cement replacement in the production of cement brick. The objectives were aimed to determine the performance of brick as the cement was replaced by SFW with various percentages through density test, compressive strength test, and water absorption test. The ratio of cement-sand and water-cement were 1:3 and 0.5 respectively followed by the replacement volume of cement which consists of SFW with 0%, 1%, 3%, 5%, 7%, and 9%. Overall findings, SFW has the potential to produce lightweight bricks. The best optimum percentage of SFW for cement brick is 1%. The result obtained by SFW1 has a higher strength value which is 16.16 MPa and a lower water absorption value which is 11.72% compared to other percentages. Nevertheless, all samples from each percentage of SFW were found to comply with the standard requirements.